Toddler Development in the Context of Malnutrition: A Systematic Literature Review - Tiffatul Jannah Firdausya (International Journal Of Health Science, 2025)
Toddlerhood is a critical period for optimizing child development, as it is a time when foundational skills in various domains are formed. Malnutrition in children, including conditions like stunting, wasting, underweight, and kwashiorkor, poses a significant threat to this development. The effects of malnutrition are not isolated to a single domain but can disrupt and hinder growth across five developmental areas: gross motor skills, fine motor skills, language, personal-social skills, and cognitive skills. This study aims to examine the developmental characteristics of toddlers suffering from malnutrition, focusing on how these conditions impact their growth. A literature review design was employed, and articles were sourced from databases such as ScienceDirect, PubMed, and SpringerLink. The article search followed the PRISMA Flow Diagram, and a total of 5045 articles were initially identified. After screening, 10 articles were selected that met the inclusion criteria and research objectives. The findings from these studies consistently revealed that malnourished toddlers exhibit delays in the five developmental domains mentioned above. These delays, particularly in motor and cognitive skills, can have long-term consequences on a child's future development. This study emphasizes the importance of addressing malnutrition in the early years, as early intervention is crucial for mitigating developmental delays and improving overall well-being in affected children.